2007
DOI: 10.1037/0012-1649.43.3.620
|View full text |Cite
|
Sign up to set email alerts
|

Working nonstandard schedules and variable shifts in low-income families: Associations with parental psychological well-being, family functioning, and child well-being.

Abstract: Longitudinal data from the New Hope Project--an experimental evaluation of a work-based antipoverty program in Milwaukee, Wisconsin--was used to explore concurrent and lagged associations of nonstandard schedules and variable shifts with parental psychological well-being, regularity of family mealtimes, and child well-being among low-income families. Working a combination of variable shifts and nonstandard hours was associated concurrently with lower teacher-reported school performance and engagement and highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 46 publications
4
78
0
Order By: Relevance
“…First, this is one of the first studies that examine the influence of immigrant parents' gendered process of adaptation on parent-child dynamics at home. Previous developmental research has linked parental work or other stress with children's psychological outcomes (e.g., Hsueh and Yoshikawa 2007) and documented the important impact of family environment on children's development (e.g., Marturano et al 2005). However, little of this research has focused on recently arrived immigrant families.…”
Section: Discussionmentioning
confidence: 98%
“…First, this is one of the first studies that examine the influence of immigrant parents' gendered process of adaptation on parent-child dynamics at home. Previous developmental research has linked parental work or other stress with children's psychological outcomes (e.g., Hsueh and Yoshikawa 2007) and documented the important impact of family environment on children's development (e.g., Marturano et al 2005). However, little of this research has focused on recently arrived immigrant families.…”
Section: Discussionmentioning
confidence: 98%
“…Variability in work schedules may lead to instability and chaos in family routines, further exacerbating negative child outcomes such as disruptions in school achievement, externalization of behavioral problems (Hsuch & Yoshikawa, 2007), and attention difficulties (Fiese & Winter, 2010). Hardway, Wilson, Shaw, and Dishion (2012) revealed that whereas positive behavior supports cultivation of the development of self-regulatory skills, household chaos acts as a deterrent to the development of many skills over time, stating that poor self-regulatory skills were related to increases in externalizing problems over time.…”
Section: Family Rolesmentioning
confidence: 97%
“…For the situational aspects of maternal suffering, bureaucratic difficulties that were experienced in different contexts were important in developing a sense of frustration and social impotence that were related to the requests and tasks that were proposed by social services (Arditti et al 2010). In these situations, the child's evolutional challenges are to cope with adversity, show his/her resourcefulness, resist threats and effectively adapt despite external personal and/or social difficulties (Hsueh and Yoshikawa 2007). The challenges of providing sensitive and structured care for children in foster care go well beyond the normative experiences of parenting (Murray et al 2011).…”
Section: Introductionmentioning
confidence: 98%